Community Reintegration of Juvenile Offenders in Vietnam: Public Perceptions, Legal Framework, and Lessons from Indonesia - Vũ Công , Giao; Nguyễn Duy Hà, Ngân (Journal of Indonesian Constitutional Law, 2025)
This article examines the community reintegration of juvenile offenders in Vietnam, with a particular focus on public perceptions, the legal framework, and policy implications, drawing on references from Indonesia. The purpose is to examine how reintegration is framed not only as a matter of criminal policy but also as a constitutional and human rights obligation, given that both the Vietnamese and Indonesian Constitutions affirm the protection of children and respect for human dignity. The contribution of this study lies in linking constitutional and human rights principles with comparative juvenile justice practices, thereby addressing a gap in existing research that often separates legal analysis from social attitudes. The study employs a combined doctrinal and comparative legal method, complemented by an exploratory survey of community attitudes in Vietnam. Findings reveal that while the statutory framework provides for diversion, non-custodial measures, and support services, gaps remain in implementation due to weak inter-agency coordination and persistent social stigma. Public perceptions strongly support educational and family-based reintegration but are more cautious toward community service and restorative justice mechanisms. Comparative insights from Indonesia highlight clearer diversion thresholds, the integration of social workers, and the role of village-level institutions in supporting reintegration. The article concludes that strengthening Vietnam's framework requires the constitutionalization of the right to reintegration, the implementation of individualized case management, the expansion of non-custodial measures, and the enhancement of public trust through effective communication strategies.